The Evolution of Environmental Marketing Strategies in the Age of Climate Awareness - Yahya Majeed Alsaad; Faiza Abdulla Ali; Baydaa Essam Abdulrahman Jasim; Aqeel Mahmood Jawad; Ghufran Waleed (Environment and Social Psychology, 2025)
With mounting environmental concerns, corporate strategies have been continuously aligned to conform with environmentally sound practices. This research investigates the influence of sustainability-driven marketing strategies on corporate environmental performance (CET), specifically on CO₂ emissions reduction, energy efficient growth, effective waste management, and consumer perception and attitudes. Employing a multi-source dataset from a combination of corporate sustainability reports, consumer surveys and third-party audits, the research investigates the outcomes from comprehensive, moderate, and limited sustainability marketing strategies. Specifically, firms that adopt more long-term and transparent environmental marketing initiatives attain significantly higher reduction rates of CO₂ emissions and energy consumption, and waste management efficiency. Additionally, consumer perception analysis showcases that greater sustainability message transparency directly correlates with improved brand trust and heightened premium willingness-to-pay for sustainable qualities in products. Moreover, digital marketing strategies are found to play an analogous role, where organizations that invested in online channels reported substantially higher public sentiment and stakeholder interaction rates. The article emphasis a on need for transparency regulations regarding sustainability claims to ensure that what businesses commit to on the environmental front aligns with real, measurable results. The results suggest that companies should integrate sustainability communication deeply into their business and not limit it to an additional marketing activity. Future studies should uncover the long-term effects of sustainability marketing, best practices in industry for sustainable marketing and how new digital technologies may shape consumer environmental behavior.